Sequential Hybrid CryoMaze Ablation versus Surgical CryoMaze Alone for the Treatment of Atrial Fibrillation (SurHyb): study protocol for a randomized controlled trial. Issue 1 (December 2016) - Eisenberger, Martin; Bulava, Alan; Kautzner, Josef; Neuzil, Petr; Mokracek, Ales; Hanis, Jiri; Dusek, Ladislav
Abstract Background Atrial fibrillation is common in patients with structural heart disease who are undergoing cardiac surgery. Surgical CryoMaze has been shown to be an effective treatment in several trials, but success rates have varied considerably, between 47–95 %. The sequential hybrid approach, combining surgical CryoMaze followed by radiofrequency catheter ablation, can achieve high freedom from atrial arrhythmias, even when rigorous methods to detect arrhythmias after the procedure are used. However, data from randomized trials comparing hybrid ablations to surgical ablations alone are lacking. Methods/Design The SurHyb study is a prospective, multicenter, randomized study. Patients with persistent or long-standing persistent atrial fibrillation will be randomized to either surgical CryoMaze alone or surgical CryoMaze followed by catheter ablation 3 months post-surgery. The primary outcome measure is arrhythmia-free survival without class I or III antiarrhythmic drugs, which will be evaluated using 7-day ECG Holter monitoring at 24 months. A total of 260 patients will be investigated from three medical centers in the Czech Republic to obtain the relevant information. Discussion This is the first randomized study that compares surgical CryoMaze alone with the staged hybrid surgical CryoMaze followed by catheter ablation in patients with persistent or long-standing persistent atrial fibrillation. These results will contribute to the optimization of the treatment for these patients. Trial registration Czech Clinical Trials Registry, cz-301020151253 . Registered on 30 October 2015.